2023
DOI: 10.3390/fermentation9070689
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Substrate Composition on the Biochemical Properties and Antioxidant Activity of Pleurotus and Agaricus Mushrooms

Panagiota Diamantopoulou,
Katerina Fourtaka,
Eirini Maria Melanouri
et al.

Abstract: The composition of the substrate is one of the most critical factors influencing the quality as well as the nutritional value and bioactive content of mushrooms. Therefore, the effects of various substrates, such as barley and oat straw (BOS), beech wood shavings (BWS), coffee residue (CR), rice bark (RB) and wheat straw (WS, control substrate), on the biochemical properties (lipid, protein, polysaccharide, glucan, ash, and mineral content, fatty acids and tocopherols composition), total phenolic compounds and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…Laccase can rapidly degrade aromatic macromolecular compounds, such as lignin, and can also contribute to the electron transport pathway during respiration. This energy contribution aids in the synthesis, transport, and accumulation of edible fungi mycelium, promoting mycelium extension and regulating fruiting body growth [ 34 , 35 ]. The addition of zinc sulfate to the formula significantly boosted laccase activity in the original mycelium of apricot abalone 6 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laccase can rapidly degrade aromatic macromolecular compounds, such as lignin, and can also contribute to the electron transport pathway during respiration. This energy contribution aids in the synthesis, transport, and accumulation of edible fungi mycelium, promoting mycelium extension and regulating fruiting body growth [ 34 , 35 ]. The addition of zinc sulfate to the formula significantly boosted laccase activity in the original mycelium of apricot abalone 6 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BOS substrate significantly enhanced the protein content of both P. ostreatus strains. Diamantopoulou et al (2023) [37] also reported that the maximum protein concentration for the carposomes of the same P. ostreatus strains was achieved when cultivated on BOS and on beech wood shavings (BWS). Following the alkaline extraction at pH 12 and precipitation at the isoelectric point (pH 4), the produced PCs had almost doubled their protein content.…”
Section: Protein Content and Extraction Yieldmentioning
confidence: 97%
“…The amount of protein reported in A. bisporus ranges from 7% to 40.5% of dry weight, while in Pleurotus spp. it ranges from 7.6% to 37.04% [61,62]. The main component of mushrooms, apart from water, is carbohydrates, which include mono-and disaccharides, polyols, polysaccharides such as β-glucans, glycogen, and chitin [63].…”
Section: Basic Composition Of Wheat Flour Mushroom Powders and Shortb...mentioning
confidence: 99%